Morphometric Comparison of the Pterional Trans-sylvian and the Pretemporal Transclinoidal Approaches to Posterior Communicating Artery Aneurysms: Anatomical Study. (1st September 2019) - Basma, Jaafar; Moore, Kenneth; Abuelem, Tarek; Krisht, Khaled; Michael, L Madison; Krisht, Ali F
Abstract: INTRODUCTION: Due to the advent of endovascular techniques, modern series of surgically treated posterior communicating (Pcom) aneurysms have shown a tendency towards higher complexity and more technical difficulties. The pretemporal approach was described as a valuable extension to the pterional approach in treating basilar apex aneurysms. Its use for clipping of ruptured Pcom aneurysms was associated with decreased ischemic complications. However, its anatomical advantages for Pcom aneurysm surgery have not been previously analyzed. METHODS: Six cadaveric heads (12 sides) underwent a sequential dissection, starting with a pterional craniotomy, and then extended to a pretemporal transclinoidal approach. In each step, the following variables were measured, taking the origin of Pcom as a focal point: (1) exposed length of the internal carotid artery (ICA) proximal to the Pcom artery, (2) exposed angular circumference of ICA at the origin of Pcom, (3) deep working area between the optic nerve and tentorium/oculomotor nerve, (4) superficial working area, (5) depth of the exposure and the (6) fronto-temporal (superior posterolateral), and (7) orbito-sphenoidal (inferior anterolateral) angles of exposure. Clinical case examples are used to illustrate the advantages of the pretemporal approach. RESULTS: Compared to the pterional craniotomy, the pretemporal transclinoidal approach increased the exposed length of the proximal ICA from 3.3 to 11.7 mm ( P = .0001), and its circumference from 5.1 to 7.8 mm ( P = .0003), allowing a 210-degree view of the ICA (vs 137.9). The deep and superficial working areas also significantly widened from 53.7 to 92.4 mm 2 ( P = .0048) and 252.8 to 418.2 mm 2 ( P = .0001), respectively; while the depth of the exposure was equivalent. The frontotemporal and the sphenosylvian angles increased on average by 17 ( P = .0006) and 10 ( P = .0037) degrees, respectively. The clinical case examples demonstrate the visual, technical and strategic advantages of the pretemporal approach as a consequence of its anatomical exposure. CONCLUSION: The pretemporal approach can be useful for complex Pcom aneurysms by providing easier proximal control, wider working space, aneurysm visualization, and more versatile clipping angles. The enhanced exposure potentially results in a higher rate of complete aneurysm obliteration and complication avoidance.